Variation for Photoperiod and Temperature Sensitivity in the Global Mini Core Collection of Sorghum - Upadhyaya, Hari D.; Vetriventhan, M.; Azevedo, Vania C. R. (Frontiers in Plant Science, 2021)
Knowledge of photoperiod and temperature sensitivity of germplasm is required to identify climate-resilient germplasm for use in crop improvement. The 242 accessions of the mini core collection and three control cultivars of sorghum [Sorghum bicolor (L.) Moench], a short-day plant (SDP) were evaluated for days to 50% flowering (DFL) and plant height in two long-day rainy and two short-day post-rainy seasons, and for grain yield and 100-seed weight in the two post-rainy seasons. Differences in DFL and cumulative growing degree days (CGDD) in the rainy and post-rainy seasons were used to identify photoperiod and temperature sensitive and insensitive accessions in the mini core collection. Results revealed 18 mini core landraces to be photoperiod and temperature insensitive (PTINS), 205 to be photoperiod sensitive and temperature insensitive (PSTINS), and 19 to be photoperiod and temperature sensitive (PTS) sources. The 19 PTS sources and 80 PSTINS sources took less DFL in the long-day rainy seasons than in the short-day post-rainy season indicating their adaptation to the rainy season and a possible different mechanism than that trigger flowering in the short-day sorghums. In all three groups, several accessions with desirable combinations of agronomic traits were identified for use in the breeding programs to develop climate-resilient cultivars and for genomic studies to identify genes responsible for the photoperiod and temperature responses.